2017
DOI: 10.1007/s40846-017-0281-x
|View full text |Cite
|
Sign up to set email alerts
|

ECG Parameters for Malignant Ventricular Arrhythmias: A Comprehensive Review

Abstract: Many studies showed electrocardiogram (ECG) parameters are useful for predicting fatal ventricular arrhythmias (VAs). However, the studies have several shortcomings. Firstly, all studies lack of effective way to present behavior of various ECG parameters prior to the occurrence of the VAs. Secondly, they also lack of discussion on how to consider the parameters as abnormal. Thirdly, the reports do not include approaches to increase the detection accuracy for the abnormal patterns. The purpose of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 52 publications
1
31
0
1
Order By: Relevance
“…The second and perhaps more important drawback of the existing ECG classification systems is their incapability of providing predictive alarms before the occurrence of abnormalities. Nevertheless, it has been proven by researchers that certain features of ECG signals reflect underlying cardiac abnormalities before the occurrences of cardiac disease [4,5]. Due to the large variety of ECG parameters, the selection of optimal predictor set is a demanding task if performed manually.…”
Section: Ecg-based Heart Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The second and perhaps more important drawback of the existing ECG classification systems is their incapability of providing predictive alarms before the occurrence of abnormalities. Nevertheless, it has been proven by researchers that certain features of ECG signals reflect underlying cardiac abnormalities before the occurrences of cardiac disease [4,5]. Due to the large variety of ECG parameters, the selection of optimal predictor set is a demanding task if performed manually.…”
Section: Ecg-based Heart Monitoringmentioning
confidence: 99%
“…Indeed, some disorders are diagnosed only after they are so severe that leave the patients with little time to take therapeutic actions [3]. An early detection of abnormal cardiac behaviors through ECG signals prior to occurrences of CVD can save lives by enabling timely preventive actions [4,5]. This is an important issue noting that sudden cardiac death (SCD), which often associates with no obvious signs and symptoms, accounts for 250, 000 to 300, 000 mortality per year in the US [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have revealed that the ECG characteristic features may reflect the underlying VTAs and have predictive value for the occurrence of VTAs event through the follow-up studies [20][21][22][23][24]. They offer the advantages of the availability of the long duration and high resolution ECG recordings prior to VTAs event that enable the possibility to investigate the mechanism that is responsible for the occurrence of VTAs.…”
Section: Prognostic Values Of Ecg Featuresmentioning
confidence: 99%
“…As a result, this section presents the review of the identified ECG characteristic features which act as important input features of the short-term VTAs prediction based on machine learning. The identified ECG parameters that have prognostic value in predicting the occurrence of VTAs are, namely: QT interval, QT interval corrected with heart rate, QT dispersion, QT dynamicity, T-wave alternans and heart rate variability [24]. Each prognostic feature is further elaborated in detail in following subsection.…”
Section: Prognostic Values Of Ecg Featuresmentioning
confidence: 99%
“…Correct VLP detection is actually considered a helpful and non-invasive diagnostic tool in patients with arrhythmogenic right ventricular cardiomyopathy for preventing malignant ventricular arrhythmias such as ventricular tachycardia and ventricular fibrillation. In fact, the prediction of ventricular tachycardia/ventricular fibrillation before their occurrence is essential to prevent delay of rescue procedures [23][24][25].…”
Section: Introductionmentioning
confidence: 99%